6-[(2-Methylphenyl)sulfanyl]-5-propylpyrimidine- 2,4(1H,3H)-dione - G. Haress, Nadia; A. Ghabbour, Hazem; A. El-Emam, Ali; Chidan Kumar, C. S.; Hoong, Kun Fun (International Union of Crystallography, 2014)
In the title pyrimidine-2,4-dione derivative, C14H16N2O2S, the dihedral angle between the six-membered rings is 77.81 (10)°. The molecule is twisted about the Cp—S (p = pyrimidine) bond, with a C—S—C—N torsion angle of -59.01 (17)°. An intramolecular C—H...S hydrogen bond generates an S(5) ring motif. In the crystal, bifurcated acceptor N—H...O and C—H...O hydrogen bonds generate inversion-related dimers incorporating R2 1(9) and R2/2(8) loops. These dimers are connected into a chain extending along the a-axis direction by a second pair of inversion-related N—H...O hydrogen bonds, forming another R2/2(8) loop. The crystal structure is further stabilized by weak intermolecular C—H...n interactions, generating a three-dimensional network.